Virtual Eye - an Intelligent Assistant for Visually impaired using Artificial Intelligence - Neha Singhal,Arpitha R, Namratha S N, Nidhi V Hegde, Sachin H Prajapathi (International Journal of Advanced Science and Technology, 2020)
There will never be a conclusion to gadgets that can be made sharper with the assistance of satisfactory innovation. The primary Problem related with optically impaired individual is that they can’t perceive any item, they can’t peruse any content and furthermore when they move anyplace, they can’t get any legal data about any obstructions in their way which may hurt them. Right now, attempt to determine these issues. We propose a wise help framework for visually impaired individuals, which are made out of wearable brilliant glasses, a smart strolling stick, cell phones application, and on-line data stage. When visually impaired individuals wear the proposed smart glasses and hold the proposed smart strolling stick, the snags can be identified. In the event that an optically impaired individual tumbles down, the related data will be recorded and transferred to the on-line data stage. Related data can likewise be seen by the proposed cell phones application. Every one of these errands are exceptionally fundamental for the protected route of blinds. It can likewise fill in as virtual eyes for the blinds. Generally, Blinds can’t peruse any content. For perusing they use Braille lipi technique that isn’t exceptionally effective. So, this smart glass can help blinds to peruse any content. A Special sort of camera which will be mounted on the glasses will catch the picture of that content which visually impaired needs to peruse, as indicated by the guidance of visually impaired. Blinds can undoubtedly hear those writings. It can catch the picture of static articles and can contrast those pictures and the put away pictures in database. What’s more, as indicated by the picture this can articulate the name of that particular article.